IMPROVING THE VOCABULARY MASTERY OF EFL STUDENTS - Fuad, Nur (LANTERN (Journal on English Language, Culture and Literature), 2013)
Learning a language means learning its vocabularies. We use the vocabularies in communication either in spoken form or written form. We try to send messages, share information and ideas by using the language. In general, no language acquisition is possible without understanding the vocabulary, either in the first or the second language (Kweldju, 2004:18).